Abnormal proliferative response of the carotid artery of spontaneously hypertensive rats after angioplasty may be related to the depolarized state of its smooth muscle cells - Dalle Lucca,S.L.D. (2000)
Hypertension is one of the major precursors of atherosclerotic vascular disease, and vascular smooth muscle abnormal cell replication is a key feature of plaque formation. The present study was conducted to examine the relationship between hypertension and smooth muscle cell proliferation after balloon injury and to correlate neointima formation with resting membrane potential of uninjured smooth muscle cells, since it has been suggested that altered vascular function in hypertension may be related to the resetting of the resting membrane potential in spontaneously hypertensive rats (SHR). Neointima formation was induced by balloon injury to the carotid arteries of SHR and renovascular hypertensive rats (1K-1C), as well as in their normotensive controls, i.e., Wistar Kyoto (WKY) and normal Wistar (NWR) rats. After 14 days the animals were killed and the carotid arteries were submitted to histomorphometric and immunohistochemical analyses. Resting membrane potential measurements showed that uninjured carotid arteries from SHR smooth muscle cells were significantly depolarized (-46.5 ± 1.9 mV) compared to NWR (-69 ± 1.4 mV), NWR 1K-1C (-60.8 ± 1.6 mV), WKY (-67.1 ± 3.2 mV) and WKY 1K-1C (-56.9 ± 1.2 mV). The SHR arteries responded to balloon injury with an enhanced neointima formation (neo/media = 3.97 ± 0.86) when compared to arteries of all the other groups (NWR 0.93 ± 0.65, NWR 1K-1C 1.24 ± 0.45, WKY 1.22 ± 0.32, WKY 1K-1C 1.15 ± 0.74). Our results indicate that the increased fibroproliferative response observed in SHR is not related to the hypertensive state but could be associated with the resetting of the carotid smooth muscle cell resting membrane potential to a more depolarized state.